THE IMPLEMENTATION OF MODERNIZATION OF THE LOCAL TAX SYSTEM AT THE SOUTH BOLAANG MONGONDOW BPKPD: PELAKSANAAN MODERNISASI LOKAL SISTEM PERPAJAKAN DI BPKPD BOLAANG MONGONDOW SELATAN - Rizka Mayulu; Djamila Podungge; Arifin Tahir (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This study aims to analyze and determine the application of themodernization of the local tax system at the South Bolaang MongondowBPKPD.The research used a qualitative descriptive approach. Data collectiontechniques are interviews, observation and documentation. Data analysistechniques consist of stages of collecting data, reducing data, presentingdata, and drawing conclusions.The results showed that the implementation of the modernization of thelocal tax system of the South Bolaang Mongondow BPKPD, namely: 1)modernizing the organizational structure through the formation of anIntegrated Supervision Team, as well as conducting inspections of servicetasks. However, the modernization of this organizational structure has notbeen implemented optimally because it has not established a one-stopservice through Account Representatives (AR); 2) modernization oforganizational procedures through simplification of administrativeprocedures and utilization of information and communication technologythrough OM OKU and Tapping Box applications; 3) modernization oforganizational strategy through campaigns and outreach on the importanceof paying taxes, as well as socialization of OM OKU and the Tapping Box.However, this socialization has not been evenly distributed across all levelsof taxpayers' society; 4) Modernization of organizational culture throughclear and firm sanctions for violations for taxpayers who do not pay taxes,providing basic training and ICT development for ICT operators, providingcomplete office infrastructure supported by clean, fragrant and comfortableoffice space conditions, so as to provide excellent service to taxpayers incarrying out their tax obligations.